Factors influencing entrepreneurs’ intention towards online business involvement - Abdul Rahman, Rozailin; Mohd Shariff, Ros Aniza (2020)
In present time, the Malaysian Government is motivated and committed to produce local entrepreneurs with high quality and entrepreneurial value. This goal is associated with the country’s economic transformation towards a fully developed nation status by the year 2020. Despite of the high potential impact of the current technology platforms, specifically for online business in Malaysia, there are local entrepreneurs that do not have the intention to utilize technology as a medium for their business and marketing development purposes. This issue, if left unchecked, will have unfavorable effects on the future growth of online local entrepreneurs in Malaysia. The integrated model of Theory Planned Behavior and the exploratory factor analysis were used in this study. This study aimed to understand the factors in influencing entrepreneurs’ intention towards online business involvement by exploring the attitude and subjective norms of the entrepreneurs. One hundred and fifty registered local entrepreneurs with Companies Commission of Malaysia were selected as respondents. The questionnaire-based survey was used for data collection. The findings are really useful for the government and concerned authorities as good as potential investors to cultivate, to review proper tools and strategically plan relevant program to ensure entrepreneurial involvement of local entrepreneurs via online could be enhanced in the business area locally and globally.